2023
DOI: 10.1007/s42250-023-00688-2
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Physicochemical Characterization of Highly-pure Amorphous Silica Nanoparticles from Locally Available Dunes Sand

Abstract: This study synthesized highly pure silica nanoparticles from the northeast Algerian Sahara dunes sand as a low-cost silica source using a simple and environmentally friendly method. The silica nanoparticles were extracted using a sodium silicate solution as a precursor without employing any additive agents. The extracted silica’s crystalline structure, chemical composition, chemical bonding, microstructure, elemental analysis, thermal analysis, and optical characteristics were investigated. The X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Additionally, oxidation of potential organic materials may occur between 200 and 400 °C (Mikhailova et al, 2022). The weight loss noticed between 530 and 740 °C was strongly linked to the calcium carbonate concentration (Meftah et al, 2023), which exceeded 0.8 % for the T1 sand sample and 2.7 % for the T2 sample. The DTA spectrum of both sand samples shows three endothermic peaks at 105, 574, and 700 °C, as well as one exothermic peak at 886 °C for T2 sand and 1014 °C appear for T1 sand.…”
Section: Thermal Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, oxidation of potential organic materials may occur between 200 and 400 °C (Mikhailova et al, 2022). The weight loss noticed between 530 and 740 °C was strongly linked to the calcium carbonate concentration (Meftah et al, 2023), which exceeded 0.8 % for the T1 sand sample and 2.7 % for the T2 sample. The DTA spectrum of both sand samples shows three endothermic peaks at 105, 574, and 700 °C, as well as one exothermic peak at 886 °C for T2 sand and 1014 °C appear for T1 sand.…”
Section: Thermal Analysismentioning
confidence: 97%
“…Desert sand contains grains ranging in size from 0.0625 to 2 mm with a typical chemical composition of SiO2 (<90 wt%), Al2O3(<16 wt%), and CaO (<20 wt%), Fe2O3, MgO, TiO2, K2O, and Na2O. Furthermore, desert sand is one of the most promising materials for producing highly pure quartz (silicon dioxide), amorphous silica, as well as Silicon (Meftah and Hani, 2022;Meftah et al, 2023). Radwan et al (2021) showed that Arabian desert sands have the potential to be used as a thermal energy storage medium and solar absorber material.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated density of the rice husk xerogel was 3.31 g/cm 3 and that of aerogel was 2.86 g/cm 3 , while those of the beach sand xerogel and aerogel were 2.88 g/cm 3 and 2.68 g/cm 3 , respectively, using the crystallographic open data (COD). The variation in the density was due to the different drying techniques employed.The aerogel is lighter than the xerogel because the supercritical extraction method aided the replacement of the liquid component of the alcogel by air.…”
Section: Density and Surface Area Of The Silica Gelsmentioning
confidence: 99%
“…where ρ represents density in g/cm 3 and d m is the crystallite diameter in nanometers. The substitution of the respective values of the density and crystallite diameters of the xerogel and aerogel yielded the specific surface area values of 122 m 2 /g and 145 m 2 /g for the xerogel and aerogel, respectively, for the rice husk, which shows an increment of 16 %.…”
Section: Density and Surface Area Of The Silica Gelsmentioning
confidence: 99%
See 1 more Smart Citation